The Influence of Javanese Political Concept of Power on President Sukarno (History Department, Semarang State University and Historian Society of Indonesia, 2021)
Various studies have shown a strong connection between political leaders’ views and practices with the culture and tradition of their upbringing. The culture and tradition would then become a prism through which the leaders understand themselves and comprehend their political dynamics while trying to play a particular role in it. This was also the case with Sukarno, the first president of Indonesia. Being born and raised on the island of Java, Sukarno was greatly influenced by the Javanese concepts of power, especially the concepts about a Javanese ruler’s self-understanding, domestic politics, and international relations. As expressed in many of his speeches and writings, Sukarno deeply understood the Javanese concept of power and tried to operate around the concept. Based on his understanding of the concept, for instance, he considered himself a Javanese ruler. As President of Indonesia, he implemented his knowledge of the Javanese concept of power in his domestic politics as well as in his relations with other nations on the world stage. The influence of the Javanese concept of power, however, was not static. It was as dynamic as to how Sukarno responded to the dynamics of Indonesian and international politics throughout his political career. Using historical and cultural approaches to Sukarno's political life, this research intends to explore how the Javanese concept of power greatly influenced Sukarno’s political views and practices. It will show that the beliefs and practices helped Sukarno unify Indonesia and obtain international prominence. At the same time, it also led him to the uncelebrated last days of his political life.Berbagai studi telah menunjukkan adanya kaitan yang kuat antara pandangan dan praktik-praktik politik seorang pemimpin politik dengan budaya dan tradisi yang telah membesarkannya. Budaya dan tradisi itu kemudian menjadi semacam prisma yang digunakan oleh sang pemimpin politik untuk memahami diri-sendiri, untuk memahami dinamika politik di sekitarnya seraya berusaha memainkan peran khusus di dalamnya. Hal ini juga berlaku untuk Sukarno, Presiden pertama Indonesia. Sebagaimana akan ditunjukkan dalam tulisan ini, sebagai seseorang yang dilahirkan di Pulau Jawa, Sukarno amat dipengaruhi oleh konsep Jawa tentang kekuasaan, terutama konsep tentang pemahaman diri seorang penguasa Jawa, tentang politik dalam negeri dan tentang hubungan internasional. Sebagaimana terungkap dalam berbagai pidato dan tulisan-tulisannya, Sukarno tidak hanya sungguh-sungguh memahami konsep kekuasaan Jawa, melainkan juga mencoba untuk memparaktikkan konsep tersebut. Berdasarkan pemahaman atas konsep kekuasaan Jawa, misalnya, ia memandang diri sebagai seorang penguasa Jawa. Sebagai Presiden Indonesia ia juga mengimplementasikan pemahamannya akan konsep kekuasaan Jawa terkait politik dalam negeri maupun hubungan dengan negara-negara lain di panggung dunia. Namun demikian pengaruh itu sama sekali tidak bersifat statis. Pengaruh tersebut bersifat dinamis, seiring dengan respon Sukarno terhadap berbagai perkembangan politik yang ada, baik di tingkat dalam negeri mapun dalam kaitannya dengan perkembangan politik dunia pada umumnya. Dengan menggunakan pendekatan historis dan kultural atas kiprah politik Sukarno, tulisan ini bermaksud untuk mengekplorasi bagaimana pandangan dan kiprah politik Sukarno sangat kuat dipengaruhi oleh konsep kekuasaan Jawa. Tulisan ini juga akan menunjukkan bagaimana pandangan dan kiprah politik Sukarno telah membantunya dalam menyatukan Indonesia dan dikenal secara internasional. Pada saat yang sama pengaruh itu juga telah membawanya ke akhir kehidupan politik yang kurang menyenangkan.